2019
DOI: 10.1136/bmjopen-2019-030028
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities for the management of broken bones of the upper limb in people over 50: a UK priority setting partnership with the James Lind Alliance

Abstract: ObjectiveTo determine research priorities for the management of broken bones of the upper limb in people over 50, which represent the shared priorities of patients, their families, carers and healthcare professionals.Design/settingA national (UK) research priority setting partnership.ParticipantsPeople aged 50 and over who have experienced a fracture of the upper limb, carers involved in their care, family and friends of patients, healthcare professionals involved in the treatment of these patients.MethodsUsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…Several PSPs have been completed for common musculoskeletal conditions [13][14][15][16][17], however none addressed rare musculoskeletal disorders. This PSP applied the JLA method to a group of rare musculoskeletal disorders in adults -FD/MAS, XLH and OI, in order to identify the most important research directions in diagnosis, treatment and long-term management.…”
Section: Introductionmentioning
confidence: 99%
“…Several PSPs have been completed for common musculoskeletal conditions [13][14][15][16][17], however none addressed rare musculoskeletal disorders. This PSP applied the JLA method to a group of rare musculoskeletal disorders in adults -FD/MAS, XLH and OI, in order to identify the most important research directions in diagnosis, treatment and long-term management.…”
Section: Introductionmentioning
confidence: 99%
“…While research priority setting for musculoskeletal conditions is reported in the literature, this is the first priority setting process to be performed specifically for common conditions affecting the hand. 17 Priority setting in broken bones of the upper limb in people over 50, 18 broken bones in older people, 19 cellulitis 20 and life after stroke 21 all have priorities that may be relevant to the hand. However, any such uncertainties will only relate to a small number of the hand disorders which present to hand clinicians.…”
Section: Discussionmentioning
confidence: 99%
“… 119 The need for identifying the appropriate outcomes was the top research requirement in a recent James Lind Alliance Priority Setting Partnership project regarding fractures in older people. 120 The development of a COS must be done in alignment with pre-existing international standards and taking into consideration patient and public opinion. 121 …”
Section: Discussionmentioning
confidence: 99%